Cave surface pollen and the palynological potential of karstic cave sediments in palaeoecology - Navarro, C. (2001)
Palynological results are presented of surface cave sediments from six caves of southeastern Spain, which differ in location, morphology, size, orientation and number of entrances. The results address several issues of pollen taphonomy in a cave environment. Modern sediments from caves contain pollen assemblages that may reflect local and regional vegetation even better than those obtained in the exterior environment. Cave geometry is an important factor affecting the quality of pollen spectra registered inside the cavity. Generally, the highest concentrations of palynomorphs are observed in the cave entrance and in sediments associated to dry depositional conditions. Speleothems and wet carbonated sediments, and those obtained from wall and rear areas often contain altered pollen spectra. Biotically transported taxa can help to provide palaeoecological information. The depositional context is extremely complex and caution should be taken in palaeoecological reconstruction. Therefore, uniform rules for sampling strategy should not be applied to all cave sediments.